SISTEM KEPERCAYAAN PAGANISME MASYARAKAT ARAB PRA ISLAM - Damayanty, Rizka; Ellya Roza, Ellya Roza (Tajdid, 2024)
The aim of writing this article is to find out about the life of Arab society before Islam came. The belief system adhered to by Arab society at that time and how Arab society worshiped by worshiping idols. Arab society before Islam came, was famous for worshiping idols, namely having many gods or gods. The worship of idols is known as "Paganism". This term is generally used to refer to the practices and traditions of pagans. In the beginning, the people of Mecca or Arab society were loyal to the teachings of Prophet Abraham and Prophet Ismail, namely worshiping only Allah SWT and not associating partners with Him. However, over time the belief in monotheism faded and many understandings and beliefs emerged. From this background, the author will discuss the belief system of pre-Islamic Arab society. The approach used by the author is collecting data specifically through writing, both historically, books, articles and various readings that help in writing. With the aim of developing both theoretical and practical aspects of its use, this paper refers to the condition of Arab society before the arrival of Islam. From the research results, the beliefs of Arab society before Islam with the Paganism belief system focused on the worship of 3 Gods known as the Trinity. The gods included in the Trinity are Al - Lata, Al - Uzza and Manat. However, these three gods have a relationship with Allah, that is, the form of worship of Allah is carried out through idols.